An Evaluation of the Communication Strategies in a Selected Health Facility - Kumassah, Catherine Makafui (UniMAC-GIJ, 2020)
Communication is an essential part of every business or organisation and should be the hub of development in the business or organization. Health organisations have created a department to address the issues including to educate, inform and keep their patients. This study sought to evaluate the communication strategies used in a selected health institution. A sample of three permanent staff were used at the Public Relations Unit. The study employed the use of semi-structured interview guide. The findings revealed that traditional media such as television, radio and newsletters was mostly used to reach the target audience. However due to the advent of technology, the hospital had added social media to have a wider reach of their audiences. The hospital reaches its internal and external publics through its website, emails, staff info sheets, circular and memos, intercom patients and info centres, interpersonal communication of face-to-face interactions, vibrant social media platforms and telephones. In view of this, it is recommended that management should train staff thoroughly in social media and communication as new trends come in daily. Digital television screens for education and information purposes should also be provided in all Units to aid information flow. Additionally, the hospital needs to look at moving to Instagram which can take about 1000 persons thereby reaching its staff and patients promptly. Most importantly, an app can be made to track to the progress of patients and staff. They can be reached after they visit the hospital to express their views, concerns and recommendations.
Thesis